Shewanella putrefaciens Pdp11 extracts promote European sea bass resistance against RGNNV infection. - Moreno-García, Patricia; Álvarez-Torres, Daniel; Gémez-Mata, Juan; Balebona-Accino, María del Carmen; Domínguez-Maqueda, Marta; Cerezo-Domínguez, Ana Isabel; Moriñigo-Gutiérrez, Miguel Ángel; Béjar-Alvarado, Julia; García-Rosado, Esther; Alonso-Sánchez, María del Carmen (My University, 2024)
The viral nervous necrosis (VNN) is a neurotropic disease affecting different fish species, resulting in high mortality rates. The causal agent is the nervous necrosis virus (NNV), belonging to the Betanodavirus genus, Nodaviridae family. Betanodaviruses are classified into four species; however, commercial vaccines are only available for RGNNV, one of the most predominant viral species isolated in the Mediterranean area. Since preventive measures against NNV infections are scarce, the development of different strategies to avoid the disease is highly relevant. Functional diets play an important role, and, in this context, the addition of probiotics to fish feed has been reported to provide several benefits to fish health. However, there are safety concerns regarding feed supplementation with live bacterial cells. In this regard, the use of non-viable probiotics it is of great interest. Shewanella putrefaciens Pdp11, SpPdp11, is a probiotic isolated from healthy gilthead seabream, which has been described to promote antibacterial activity; however, its antiviral activity remains poorly understood. Recently, our research team evaluated the anti-RGNNV effect of SpPdp11 sonicated extracts in vitro. In the present study, the effect of feed supplementation with sonicated extracts of SpPdp11 has been evaluated in European sea bass, as well as its effect against an RGNNV challenge. Animals were fed for 30 days with the supplemented diet and the results were compared with a control diet. Changes in the intestinal microbiota and in the transcription of immune genes were assessed at 7 and 30 days within the feeding period. Animals fed with the supplemented diet show higher levels of prokaryotic diversity; however, these differences were not statistically significant. Regarding transcriptional analyses, only 8 of 56 genes were differentially transcribed in fish fed with the supplemented diet, all of them downregulated.
Keywords: Lubinas - Enfermedades por virus - Congresos; Dicentrarchus labrax; Shewanella putrefaciens Pdp11; Betanodavirus; Lubina